Słownik polsko-łaciński jako narzędzie dydaktyczne. Analiza dostępnych pozycji pod kątem ich przydatności dla osób uczących się języka łacińskiego - Rogowska-Wandowicz, Anna (Collectanea Philologica, 2025)
Dictionaries are among the important materials used in language learning and teaching. The aim of this article is to examine the available Polish-Latin dictionaries from the point of view of their usefulness for native speakers of Polish in the process of Latin acquisition. As a reference, I use Monika Bielińska’s work “Leksykografia. Słownik specjalistyczny” (“Lexicography: A Specialist Dictionary”). In the course of the paper I present the needs of the two most important groups of addressees of the Polish-Latin dictionary, namely students of classical philology and participants in Latin classes in other study programmes (e.g. law, medicine). I analyse the advantages and disadvantages of two dictionaries: “Mały słownik polsko-łaciński” (“Compact Polish-Latin Dictionary”) edited by Lidia Winniczuk and “Słownik polsko-łaciński” (“Polish-Latin Dictionary”) by Antoni Bielikowicz. The conclusion of the study is that there is no dictionary that is well suited to the needs of either of the target groups, and for philology students, the best choice may be to reach for Bielikowicz’s 19th-century dictionary.